Performance of passively Q-switched ring erbium-doped fiber laser using a multiwalled carbon nanotubes polyethylene oxide (PEO) polymer composite-based saturable absorber - Haris, H.; Anyi, C.L.; Muhammad, A.R.; Ahmad, F.; Nor, R.M.; Zulkepely, N.R.; Ali, N.M.; Harun, Sulaiman Wadi; Arof, Hamzah (Wiley Black, 2015)
The aim of this article is to report the fabrication and characterization of dispersed multiwalled carbon nanotubes (MWCNTs) polymer composites and use them as passive SAs in Q-switched Erbium-doped fiber (EDF) for ultrafast laser generation at 1.5-mu m region. CNT polymer composites were fabricated into thin films by homogenizing different concentrations (1.8, 4.8, and 10.1 wt. ) of MWCNTs with host polymers polyethylene oxide. The fabricated thin film was then deposited between two fiber connectors as passive SA and incorporated into fiber laser's ring oscillator. The EDFL exhibited a central wavelength of 1560.5 nm when pump power is fixed at 42 mW. The Q-switching operation starts at the lowest threshold of 39.3 mW for all the three different SA concentrations. For 1.8 wt. MWCNTs concentration, the pulse repetition rate of the Q-switched EDFL is started from 35.6 kHz, while for 4.8 wt. and 10.1 wt. , the pulse repetition rate started at 78.5 and 66.1 kHz, respectively. At the MWCNTs concentration of 1.8 wt. , the pulse energy of the Q-switched EDFL increases from 7.9 to 24.7 nJ as the pump power increases from 39.3 to 58.8 mW. (c) 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1897-1901, 2015